(untitled) (Journal of the College of Basic Education, 2022)
The aim of this research is designing and implementing proposed steganographic method. The proposed steganographic method don’t use a specific type of digital media as a cover but it can use all types of digital media such as audio, all types of images, video and all types of files as a cover with the same of security, accuracy and quality of original data,considering that the size of embedded data must be smaller than the size of a cover. The proposed steganographic method hides embedded data at digital media without any changing and affecting the quality of the cover data. This means, the difference rate between cover before hiding operation and stego is zero. The proposed steganographic method hides embedded data at various locations in cover irregularly or randomly, whereas the locations of cover for information hiding are not constant, this property will increase the level of security for proposed method. In the proposed method, the sender needs sending a file that has small size via any communication channel and that considered as a key while sending a cover is not necessary to recipient if both agree about downloading it from the internet before sending a file. The contents of this file are invaluable for an attacker. The programming language that used in programming this proposed method is C++ language. Steganographically, The proposed steganographic method is strong and robust. It is possible classifying this proposed method as a public key steganography system and substitutionsystem at the same time.